Dust Sensors for Cotton Processing Plants and Their Use - o’g’li, Tursunov Ahror Aminjon (Journal of Marketing and Emerging Economics, 2022)
The article discusses the calculation of pulses left by dust particles in a given unit of time, the range of detection of dust particles, graphs of changes in sensor values under the influence of a certain temperature, the results of error evaluation.